2022
DOI: 10.3390/app12041943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of X-ray Fluorescence (XRF) and Atomic Absorption Spectrometry (AAS) Results for an Environmental Assessment at a Mercury Site in Kyrgyzstan

Abstract: Khaidarkan, Batken Province, Kyrgyzstan is home to one of the world’s largest and last primary mercury mines. Doctors without Borders (MSF) and the Ministry of Health (MOH) of Kyrgyzstan have found that the Batken region has an elevated rate of non-communicable diseases (NCD) within the country. NCD can be caused by environmental pollution. A human health risk assessment was conducted to investigate heavy metal exposure. Using a hand-held X-ray fluorescence (XRF) spectrometer for soil screening is faster and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…With the aid of the manufacturer, the XRF was calibrated with the ICP-OES results (R 2 = 0.99) and using the Olympus Vanta blank in zipper plastic #2. Furthermore, previous published studies have demonstrated the reliability and comparability of the XRF device to traditional approaches like the ICP-OES [4,[6][7][8]17,18,[39][40][41][42][43][44][45][46]. The motivation for using the XRF stems from its portability for environmental monitoring at remote sites where laboratories are not readily available [47,48].…”
Section: Field Samplingmentioning
confidence: 99%
“…With the aid of the manufacturer, the XRF was calibrated with the ICP-OES results (R 2 = 0.99) and using the Olympus Vanta blank in zipper plastic #2. Furthermore, previous published studies have demonstrated the reliability and comparability of the XRF device to traditional approaches like the ICP-OES [4,[6][7][8]17,18,[39][40][41][42][43][44][45][46]. The motivation for using the XRF stems from its portability for environmental monitoring at remote sites where laboratories are not readily available [47,48].…”
Section: Field Samplingmentioning
confidence: 99%
“…In the Pb-Zn site, Hg was in the 0.03-0.12 mg/kg interval according to the analysis performed by means of DMA-80, whereas the pXRF output was 33-280 mg/kg. The occurrence of false positives for Hg from pXRF is known to occur [18], and they can be removed after manual observation of the spectra. However, in the Cu-Sb site, Hg (up to 473 mg/kg-"quantitative") determination was better than Cr (up to 182 mg/kg-"qualitative").…”
Section: Validation Assessment: Pxrf Vs Icp-ms and Dma-80mentioning
confidence: 99%
“…In the last decades, many studies [7,11,[13][14][15][16][17] have reported the performance of pXRF instruments based on QA/QC validation procedures using certified reference materials (CRMs), blank samples, and/or traditional laboratory analyses on site-specific samples, studying different groups of elements in various matrices. Moreover, pXRF analyses of soil, lato sensu, samples are usually performed on common elements such as base metal(loid)s (e.g., As, Cu, Fe, Mn, Pb, Zn), whereas, curiously, highly toxic elements such as Hg and Sb have not been considered or have not been found in concentrations high enough and were detected in a small number of studies, e.g., [18,19]. Thus, the main purpose of this research was to evaluate the advantages and disadvantages of the use of pXRF on samples collected from two different decommissioned mining areas in Italy characterised by Pb-Zn and (Hg-rich) Cu-Sb ore deposits found to have very low to very high concentrations of As, Cu, Hg, Pb, Sb, and Zn.…”
Section: Introductionmentioning
confidence: 99%